COOPERATION BETWEEN THE REPUBLIC OF INDONESIA AND THE UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) IN ADDRESSING SANITATION AND DRINKING WATER PROBLEMS IN NORTH SUMATERA - Muthiah Dhuhaa Sakinah; Indra Pahlwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research examines the collaboration between the United States Agency for International Development and Indonesia in dealing with sanitation and clean water issues, specifically in North Sumatra. The problem of clean water and sanitation is still a major obstacle in Indonesia. Therefore, through USAID, the United States government provides grant assistance to Indonesia through the IUWASH PLUS Program. This study aims to determine the partnership between North Sumatra province and USAID through the IUWASH PLUS (Indonesia Urban Water, Sanitation and Hygiene Penyehatan Lingkungan untuk Semua) program. This study employs a qualitative approach, drawing on the idea of foreign aid in the form of grants and Neoliberalism at the level of nation-state analysis. The study is descriptive research. Thus, the researcher collects the data through library research techniques. The findings reveal that the USAID IUWASH PLUS program effectively improves clean water and sanitation services in North Sumatra, referring to the results published by USAID IUWASH PLUS through the Final Book in June 2022. Keywords: USAID, IUWASH PLUS, Foreign aid, Clean water, Sanitation, North Sumatra, Drinking Water, Indonesia